Effect of Drainage on Moisture Relations of a Heavy Clay Soil - Yadav, J. S. P. (Indian Forester, 1961)
With a view to studying the effect of draining on the moisture relations of a heavy day soil, an investigation was carried out in a forest area over Oxford clay in the region of Waterperry, England. The tensiometers, nylon resistance units and tension apparatus prepared by the author for use in this investigation have been described in detail with illustrations. The readings of tensiometers and nylon resistance units at different depths in the drained and undrained soils subjected to wetting and drying cycles, suggested that at a given tension the drained soil with better structure is associated with a higher level of available moisture as compared to the undrained soil with poorer structure.